Perceived effects of N-power agro programme on youth empowerment and income generation in Lagos state, Nigeria - Komolafe, O.D.; Taiwo, A. M.; Fapojuwo, O. E.; Oyewole, A.Q. (ADAN JOURNAL OF AGRICULTURE, 2024)
The study examined the effect of N-power Agro program on youth empowerment and income generation in Lagos state, Nigeria. The objectives of the study were to examine the socio-economic characteristics of N-power agro beneficiaries, to determine the contribution of N-Agro to empowerment, to ascertain how N-Power agro programme generates income for the youths and to know the problems affecting N-Power Agro programs in Lagos state. A three-stage sampling technique was used to select one hundred and twenty (120) respondents. Data were collected using structured questionnaire and analysed with descriptive and inferential statistics such as frequency counts, percentages, mean and Analysis of Variance. The mean age of the respondents was 26 years, 55.0% were male, 50.8% were married and 42.5% were First Degree holders. Findings also revealed that 80.0% felt the programme has improved their working experience, 79.2% indicated that the programme has helped in poverty reduction while 62.5% perceived that the programme ensured their financial independence. The major problems affecting the implementation of N-Power Agro programmes in Lagos State are non-payment of stipend to participants as at when due ( ̅= 2.92), insufficient information ( ̅= 2.68) and high transportation fare paid by the participants to work ( ̅= 2.63). The study also revealed that there is a significant relationship between N-Power Agro and youth empowerment in Lagos State. It is therefore recommended that government should ensure adequate provision of funds for income- generating projects through the N-Power programmes. This will solve the problem of delay in the payment of the stipend.